Deteksi keberadaan bakteri pengkontaminasi pangan Salmonella sp. pada telur - Risdayanti, Risdayanti; Latif, Ulfa Triyani A; Wirawan, Hadi Purnama (Filogeni: Jurnal Mahasiswa Biologi, 2023)
Eggs are a source of animal protein which can be contaminated by pathogenic microorganisms such as Salmonella sp. which is dangerous to human health. The aim of this research is to determine the presence of Salmonella sp bacteria. on chicken eggs. This research was carried out using chicken egg samples which were then tested at the Public Health Laboratory of the Balai Besar Veteriner Maros using 3 selective media for colony growth, namely Xylose Lysine Deoxychoalate agar (XLD), Hektoen Enteric agar (HE) and Bismuth Salt Agar (BSA) media. The results obtained showed that the 3 test media used showed negative results or no growth of Salmonella sp. bacteria, so it can be concluded that the egg samples tested in this study were not contaminated with the pathogenic bacteria Salmonella sp..